Effect of heating scan strategy using low energy density on relief of thermal residual stress in L-PBF process for CoCrMo alloy - Gyung Bae Bang; Seung Jun Han; Jung Hyun Park; Won Rae Kim; Hyun-Su Kang; Soong-Keun Hyun; Hyung-Ki Park; Taeg Woo Lee; Hyung Giun Kim (Journal of Materials Research and Technology, 2024)
This study investigates the effects of low energy density laser rescanning of Additive Manufacturing (AM) called Laser-Powder Bed Fusion (L-PBF) on the microstructure, residual stresses, and mechanical characteristics of CoCrMo alloy specimens. Specimens were fabricated under four conditions, i.e., secondary laser scanning with energy density 5 %, 10 %, and 20 %, compared to the first laser irradiation energy densities (AB, 19.41 J/mm3). To confirm the effect of the second laser irradiation, the phase change was analyzed using X-ray diffraction (XRD), and the shape and distribution of the face-centered cubic (FCC) and hexagonal closed packing (HCP) phases were confirmed through electron backscatter diffraction (EBSD) analysis. In particular, the correlation between microstructural stability and residual stress reduction was analyzed, and the effects of microstructural changes on mechanical properties were studied. Through this study, it was confirmed that the appropriate laser conditions during the L-PBF process can act as a heat source, resulting in a heat treatment effect.